1994
DOI: 10.2466/pr0.1994.75.3.1163
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Anger in Psychiatric Inpatients and Normal Subjects

Abstract: The mean anger scores of psychiatric inpatients (n = 110) on the State-Trait Anger Scale were compared with those of nonpatients (ns = 64 and 59). The inpatient group had significantly higher scores on the two measures of anger. No significant differences were found among the psychiatric diagnostic subgroups, but patients with affective disorders had scores much lower than individuals with personality disorders. Relatively high reliability was found for the trait-anger scores of psychiatric patients taken one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Finally, our study provides information about differences between clinical and nonclinical samples regarding the experience and management of anger. First, our study replicates previous studies showing that patients tend to experience anger more intensely and more frequently than people from the general population and are more inclined to express their anger both outwardly by means of physically and verbally aggressive behavior and inwardly by suppressing anger or holding anger in (Barbour et al., ; Cullari, ; De‐Mojá & Spielberger, ; Etzler et al., ; Spielberger, ). Notably, no differences were found between patients and the general population sample regarding the control of anger.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Finally, our study provides information about differences between clinical and nonclinical samples regarding the experience and management of anger. First, our study replicates previous studies showing that patients tend to experience anger more intensely and more frequently than people from the general population and are more inclined to express their anger both outwardly by means of physically and verbally aggressive behavior and inwardly by suppressing anger or holding anger in (Barbour et al., ; Cullari, ; De‐Mojá & Spielberger, ; Etzler et al., ; Spielberger, ). Notably, no differences were found between patients and the general population sample regarding the control of anger.…”
Section: Discussionsupporting
confidence: 89%
“…One study of Cullari () showed that psychiatric outpatients scored higher on the State and Trait anger scales compared with normal subjects, but it did not include the expression scales. Another study, by Etzler, Rohrmann, and Brandt (), showed higher scores on Anger Expression‐In for inmates compared with the mean of the German standardization sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in people with schizophrenia, negative self-evaluation is correlated with more severe positive symptoms (Barrowclough et al, 2003). In people with delusions, distress is correlated with the severity of the delusions (Lysaker, Lancaster, Nees, & Davis, 2003) and high levels of anger are often recorded (Cullari, 1994; Siris, 1995). More recently, Freeman and Garety (2003) have challenged the accepted view and suggested that emotions directly cause delusions.…”
Section: Volitional and Emotional Factors Undermining Motivationmentioning
confidence: 99%
“…High levels of anger are reported in schizophrenia (Cullari, 1994) and anger is associated with poorer outcomes including violence and aggression (Fassino et al, 2009). Despite the importance of anger in understanding outcomes and risk in psychosis, it is under researched.…”
Section: Introductionmentioning
confidence: 99%